Common fragile site instability in normal cells: Lessons and perspectives. Issue 5 (21st December 2018) - Palumbo, Elisa; Russo, Antonella
Abstract: Mechanisms and events related to common fragile site (CFS) instability are well known in cancer cells. Here, we argue that normal cells remain an important experimental model to address questions related to CFS instability in the absence of alterations in cell cycle and DNA damage repair pathways, which are common features acquired in cancer. Furthermore, a major gap of knowledge concerns the stability of CFSs during gametogenesis. CFS instability in meiotic or postmeiotic stages of the germ cell line could generate chromosome deletions or large rearrangements. This in turn can lead to the functional loss of the several CFS‐associated genes with tumor suppressor function. Our hypothesis is that such mutations can potentially result in genetic predisposition to develop cancer. Indirect evidence for CFS instability in human germ cells has been provided by genomic investigations in family pedigrees associated with genetic disease. The issue of CFS instability in the germ cell line should represent one of the future efforts, and may take advantage of the existence of sequence and functional conservation of CFSs between rodents and humans.